Negotiating the Descriptive–Normative Frontier of Complexity Research in the Anthropocene - Leach, Michael C. (Frontiers in Physics, 2021)
This mini-review article offers a commentary on a singular analytical problem facing legal scholars who use complexity theory and methods in legal research on climate change and the ‘Anthropocene’. It positions such research as a sub-set of complexity scholarship in law, which is generally faced with the methodological and analytical challenge of negotiating and reconciling empirical description with normative prescription. It argues that this challenge is particularly acute for legal scholars writing on climate change and the Anthropocene. Using examples from scholars writing about ‘Earth Systems Law’, it demonstrates how a heavy reliance on complexity-based empirical data as source material for normative claim-making can distract scholars from important but difficult questions about normative legitimacy and how legal change happens at multiple-levels. The special epistemological challenges posed by climate change and the Anthropocene should demand that scholars writing in this domain be especially mindful and explicit of how they link complexity descriptions to the normative claims they make, both for the sake of scientific credibility as well as for the legitimacy and viability of their propositions.